Clinical Regenerative Medicine in Urology (Springer Singapore, 2018)
This multidisciplinary book provides up-to-date information on clinical approaches that combine stem or progenitor cells, biomaterials and scaffolds, growth factors, and other bioactive agents in order to offer improved treatment of urologic disorders including lower urinary tract dysfunction, urinary incontinence, neurogenic bladder, and erectile dysfunction. In providing clinicians and researchers with a broad perspective on the development of regenerative medicine technologies, it will assist in the dissemination of both regenerative medicine principles and a variety of exciting therapeutic options. After an opening section addressing current developments and future perspectives in tissue engineering and regenerative medicine, fundamentals such as cell technologies, biomaterials, bioreactors, bioprinting, and decellularization are covered in detail. The remainder of the book is devoted to the description and evaluation of a range of cell and tissue applications, with individual chapters focusing on the kidney, bladder, urethra, urethral sphincter, and penis and testis.